Development of a Book Lending Information System Using the Rapid Application Development Model - Hidayati, Nur (IJISTECH (International Journal of Information System and Technology), 2024)
The library is an important part that must exist in the school. With a library, it is of course hoped that it can foster students' interest in reading and enrich students' knowledge. Even in this era, all types of information can be obtained anywhere and at any time with the increasingly rapid development of information technology. However, there are still many students who cannot enjoy the ease of getting this information. And there are still many schools that do not have libraries. Even if there is, the library is still very conventional. Where library data processing starts from processing book data, data on borrowing and returning books is done manually. This can cause problems in the library, such as notes written using handwriting, which can cause errors in reading if the writing is not clear. Besides that, documents in the form of cards or paper are often damaged and searching for data takes a long time. If this happens continuously it will certainly have negative impacts in the future. Therefore, schools with such conditions require the development of a library information system, especially for borrowing books. In carrying out system development, it is necessary to determine the right model to help carry out the development and so that the objectives of system development can be achieved. One of these models is the Rapid Application Development (RAD) model. In the RAD model we can clearly understand the steps that must be taken in developing a book lending information system, so it is hoped that a Book Lending Application can be produced so that it can help manage book lending information system data.